Development of Problem-Based Learning Devices to Facilitate the Mathematical Problem-Solving Skills of Class IX SMP/MTs Student - Seftia Wulan Dari; Sehatta Saragih; Armis (Journal of Research on Mathematics Instruction (JRMI), 2022)
Aware of the importance of the role and function of mathematics, the quality of mathematics learning needs serious attention to achieve the goals set. Mathematical problem-solving skills are important abilities that students must possess to solve a problem. Currently, the Mathematical Problem Solving Ability (KPMM) of students in Indonesia is relatively low. The cause of the low KPMM students is that students only memorize the formulas the teacher gives without understanding the systematic concepts in implementing learning. Another thing is that students have not been able to do questions different from the teacher's example questions. KPMM can be developed by implementing learning, namely by allowing students to solve problems related to daily life. Problem-Based Learning (PBL) was chosen as a learning innovation to facilitate KPMM. In its implementation, PBL needs to be supported by good mathematics learning tools. Therefore, this study aims to develop mathematics learning tools in the form of Silbus, Learning Implementation Plan (RPP), and Student Activity Sheet (LAS) using the PBL model to facilitate KPMM for grade IX junior high school / MTs students who are valid and practical. The development model used is the 4-D model.